The influence of the card sort method on students' learning outcomes in fiqh class - Wulandari, Adinda; Nurkolis (Penelitian Ilmu Pengetahuan Sosial, 2025)
Background: The Card Sort method, a student-centered active learning strategy, has been widely studied for its effectiveness in improving understanding and retention of information. This study investigates the impact of the Card Sort method on the learning outcomes of Fiqh students at MI Ma’arif NU 02 Bantarbarang Purbalingga. The research aims to determine whether the implementation of this method results in significant improvements compared to traditional teaching approaches. Methods: This research employs a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Pretest-Posttest Design. The study population consists of all sixth-grade students, with a purposive sampling technique selecting Class VI A as the experimental group and Class VI B as the control group. Data were collected through questionnaires and tests, and analyzed using simple linear regression and the Independent Sample T-Test in SPSS version 23. Findings: The results indicate that the Card Sort method significantly influences students’ Fiqh learning outcomes. The experimental group, which used the Card Sort method, achieved an average final test score of 79.40, while the control group, which relied on conventional methods, scored 75.40. Statistical tests show a p-value of 0.000 (< 0.05), confirming the significant effect of the Card Sort method. Additionally, the T-Test results (t = 8.448 > 2.010) further support the rejection of the null hypothesis (H0), proving that the method enhances student learning outcomes. Conclusions: The study concludes that the Card Sort method effectively improves student learning outcomes compared to conventional methods in Fiqh education. Students in the experimental group demonstrated higher engagement, better understanding, and improved test performance. To further optimize learning outcomes, students should be encouraged to actively participate in class activities, while teachers should implement creative teaching strategies and diverse instructional media. Novelty/Originality of this Article: This study contributes to the field of active learning strategies in religious education, specifically in Fiqh learning, which has been less explored in previous studies.